From Bayt to Stanza: Arabic Khayāl and the Advent of Italian Vernacular Poetry. (2nd January 2020) - Ladha, Hassanaly
ABSTRACT: At the twilight of Arabic literary culture in thirteenth-century Sicily, poets writing in the vernacular Italian use the term "stanza, " meaning a "dwelling, " to refer to a lyric strophe. Since there is no precedent for this use of the term "stanza" to refer to poetry, I suggest that "stanza" presents as a calque for Arabic "bayt, " meaning "dwelling" and a "unit of verse." To understand how the implied relation between poetry and architecture might frame new approaches to the scuola siciliana, I examine the imbrication of linguistic and built form in Arabic poetry. The qaṣīdah, the preeminent Arabic lyric, often begins with an evocation of an architectural ruin, the effaced "dār" or "bayt" of a departed beloved. I argue that her phantom form or "khayāl, " haunting and taking the place of her ruined dwelling, articulates the fluidity of all apparently enduring structures and the performative power of poetry to delineate the real. Turning to the epistemological continuities between Arabic and Italian poetry, I study the relation between architecture, phantasms, and the theory of form in the work of Giacomo da Lentini, a poet-scribe in the court of Frederick II, concluding that the kinship between the qaṣīdah and sonnet subverts "Western" narratives of self-invention and cultural authenticity.